Kapasitas Kelembagaan Badan Usaha Milik Desa dalam Pengelolaan Unit Simpan Pinjam di Desa Koto Pait Beringin Kecamatan Talang Muandau Kabupaten Bengkalis - Yupita, Sles; Afrizal, Afrizal (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research aims to determine the capacity of Village-Owned Enterprises (BUMDes) in managing Savings and Loans Units (USP) for many bad loans carried out by the community as users of savings and loans. And knowing the inhibiting and supporting factors in the process of managing savings and loan units. The theory used to measure the capacity of an organization is the Capacity theory written by Milen (2001). The method used in this research is descriptive qualitative. Data collection techniques are carried out through observation, interviews and documentation. The results of this research show that BUMDes administrators have good capacity, this can be seen from their human resources (HR) having knowledge of the existence of BUMDes, understanding of the tasks given, and the ability to complete responsibilities. The lack of awareness of the people selected as savings and loan users in paying installments is an inhibiting factor in managing savings and loan units. For this reason, the Koto Pait Beringin BUMDes Management is expected to be more wise in carrying out checks on the acceptance of prospective savings and loan users so that in the future there will be no more problems in paying savings and loan installments.